1999
DOI: 10.1046/j.1524-4741.1999.005001022.x
|View full text |Cite
|
Sign up to set email alerts
|

Mammographically Occult Breast Cancers

Abstract: A small percentage of breast cancers are not visible on mammography. Since mammographically occult malignancies may be more difficult to diagnose, we hypothesized that the lack of visualization would cause a delay in detection, more aggressive surgical and adjuvant therapy, and poorer outcome. Patients with mammographically occult malignancies were compared to patients with cancers visible on mammogram. The significance of mammographic visibility for treatment and local and distant recurrence rates were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Tarter et al [5] reported that 11% (91 of 813) of breast cancer in their series could not be found with mammography. They also reported that false-negative results are associated with lower age, weight, and parity.…”
Section: Discussionmentioning
confidence: 90%
“…Tarter et al [5] reported that 11% (91 of 813) of breast cancer in their series could not be found with mammography. They also reported that false-negative results are associated with lower age, weight, and parity.…”
Section: Discussionmentioning
confidence: 90%
“…This is in line with the finding of McKinney et al, in which the distribution of cancer type was not significantly different between AI-detected and radiologist-detected cancers [ 21 ]. In previous studies, invasive carcinomas were more likely to be mammographically occult compared with DCIS [ 5 , 28 ], and most of the cancers detected only by an AI software were invasive cancers [ 21 ]. Another study also showed that the sensitivity of an AI software was higher in invasive cancers than in DCIS [ 10 ].…”
Section: Discussionmentioning
confidence: 99%